Burial societies in rural Ethiopia - Dercon, Stefan; Hoddinott, John F.; Krishnan, Pramila; Woldehanna, Tassew (University of Pennsylvania Press, 2011)
In doing so, the chapter builds on research addressing how poor households respond to shocks; see Morduch (2005) and references therein, the review paper by Skoufias and Quisumbing (2005), and the recent collection edited by Dercon (2005). These show that in the face of shocks households can partially smooth consumption, but not perfectly; as might be expected, idiosyncratic shocks (for instance, low or late rainfall on household plots) are more likely to be insured collectively than are generalized shocks (such as low rainfall on most plots in the village). In most empirical studies of risk smoothing—for example, that of Townsend (1994)—the insurance unit has been assumed to be the village. Studies using Townsend's approach have often found that households are able to cope with idiosyncratic shocks but not covariate shocks, implying that local insurance mechanisms are inadequate to cope with aggregate shocks. More recent studies (for example, that of Munshi and Rosenzweig 2005) have begun to question the assumption that the appropriate unit of risk smoothing is the village. They suggest that consumption is smoothed within subcaste networks that extend beyond the village. Indeed, the literature on migration and remittances suggests that networks can cross geographic boundaries, with the formation of migrant networks at destination sites affected by shocks in the original locality (Munshi 2003).